2022
DOI: 10.3390/ijms23158680
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evolution of Delta (B.1.617.2) and Omicron (BA.1) Spike Glycoproteins

Abstract: The vast amount of epidemiologic and genomic data that were gathered as a global response to the COVID-19 pandemic that was caused by SARS-CoV-2 offer a unique opportunity to shed light on the structural evolution of coronaviruses and in particular on the spike (S) glycoprotein, which mediates virus entry into the host cell by binding to the human ACE2 receptor. Herein, we carry out an investigation into the dynamic properties of the S glycoprotein, focusing on the much more transmissible Delta and Omicron var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Together with the 3D model, through the web portal there is also a short MD trajectory available, 100 ns long, for each analyzed variant. Even though a better understanding of the structural and dynamic perturbation of the system is obtained with longer simulations (see results with one microsecond reported in recent works) [ 34 , 35 , 36 ], we found that interesting features can be inferred by them.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…Together with the 3D model, through the web portal there is also a short MD trajectory available, 100 ns long, for each analyzed variant. Even though a better understanding of the structural and dynamic perturbation of the system is obtained with longer simulations (see results with one microsecond reported in recent works) [ 34 , 35 , 36 ], we found that interesting features can be inferred by them.…”
Section: Resultsmentioning
confidence: 56%
“…The 3D protein models of the WT and the mutated spike were initially built by homology modeling using the web tool SWISS-MODEL [ 35 ]. The reference sequence used to align and model the missing atoms of the pre-fusion form of the cryo-EM structure (PDB ID: 6VYB) [ 36 ] was NCBI YP_009724390.1 (UniProt: P0DTC2 SPIKE_SARS2). In this structure, the RBD of the second monomer was in the up conformation, also known as open conformation, which favors the interaction with the ACE2 receptor.…”
Section: Methodsmentioning
confidence: 99%
“…Deletion of any of these three glycans favors the RBD down conformation [4,45,46]. Molecular dynamics simulations suggest that the differences in the complex glycanprotein networks between D614G, Delta and Omicron variants can control the flexibility of the RBD domain [47]. The increase in the maximum neutralization observed for the D614G N343Q and N234Q pseudoviruses suggests that a subset of the WT D614G pseudovirus stock that resist neutralization by these antibodies may have glycan modifications at these residues that facilitate evasion of neutralization.…”
Section: N-glycans Deletions Can Alter the Potency Or Completeness Of...mentioning
confidence: 99%
“…The dynamic properties of the S protein, particularly the much more transmissible Delta and Omicron variants were reported. The more mutations have accumulated in the Omicron S proteins, including the RBD [29,30]. The mutations in the receptorbinding domains (RBDs) of the S protein influence its affinities to ACE2 [31].…”
Section: Introductionmentioning
confidence: 99%